Role of bimodal stimulation for auditory-perceptual skills development in children with a unilateral cochlear implant - MARSELLA, P. (Acta Otorhinolaryngol Ital, 2015)
This is a prospective randomised study that evaluated the differences arising from a bimodal stimulation compared to a monaural electrical stimulation in deaf children, particularly in terms of auditory-perceptual skills development. We enrolled 39 children aged 12 to 36 months, suffering from severe-to-profound bilateral sensorineural hearing loss with residual hearing on at least one side. All were unilaterally implanted: 21 wore only the cochlear implant (CI) (unilateral CI group), while the other 18 used the CI and a contralateral hearing aid at the same time (bimodal group). They were assessed with a test battery designed to appraise preverbal and verbal auditory-perceptual skills immediately before and 6 and 12 months after implantation. No statistically significant differences were observed between groups at time 0, while at 6 and 12 months children in the bimodal group had better scores in each test than peers in the unilateral CI group. Therefore, although unilateral deafness/hearing does not undermine hearing acuity in normal listening, the simultaneous use of a CI and a contralateral hearing aid (binaural hearing through a bimodal stimulation) provides an advantage in terms of acquisition of auditory-perceptual skills, allowing children to achieve the basic milestones of auditory perception faster and in greater number than children with only one CI. Thus, "keeping awake" the contralateral auditory pathway, albeit not crucial in determining auditory acuity, guarantees benefits compared with the use of the implant alone. These findings provide initial evidence to establish shared guidelines for better rehabilitation of patients undergoing unilateral cochlear implantation, and add more evidence regarding the correct indications for bilateral cochlear implantation.